Silent Neuroleptic Malignant Syndrome: A Case Report of Atypical Antipsychotic Induced Elevation of Creatinine Kinase and Altered Mental Status - Amber N. Edinoff; Hamza Mohammad-Amin; Amira S. Odisho (Health Psychology Research)
34-year-old African American male with a diagnosis of schizophrenia was placed on aripiprazole and risperidone for psychosis and mood stabilization. Two days after medication initiation, the patient's mentation was altered and he appeared confused with an elevated creatine kinase (CK) at 7101. Medications were held and CK normalized with IV fluids. Quetiapine was initiated after medical stabilization along with lithium and paliperidone palmitate injections. After the second dose of paliperidone palmitate, the patient's mentation was altered, and repeat CK was 4272. The patient received 4 liters of IV fluid and his mental status returned to baseline.